Is BCG vaccination causally related to reduced COVID-19 mortality? - Masayuki Miyasaka (WILEY, 2022)
The ongoing severe acute respiratory sickness coronavirus 2 (SARS-CoV-2) pandemic has resulted in more than 3,600,000 detected cases of COVID-19 illness and nearly 260,000 deaths worldwide as of May 6, 2020. Recently, BCG vaccination was shown to correlate with reduced COVID-19 case fatality rates (preprint: Miller et al, 2020; preprint: Sala & Miyakawa, 2020; ). The most recent data from publicly available resources also indicate that both COVID-19 incidence and total deaths are strongly associated with the presence or absence of national mandatory BCG vaccination programs. As seen in Table 1, seven of eight countries with very low numbers of total deaths (< 40 per 1 million population) adopted a mandatory BCG vaccination program using one of a set of 6 separate BCG strains (Table 1). In contrast, COVID-19 mortality was markedly higher in countries where BCG vaccination is not widely administered or is given only to high-risk groups. COVID-19 mortality was also higher in countries where widespread BCG vaccination was discontinued more than 20 years ago and in countries that used the BCG Denmark strain regularly or temporarily. This raises the question of whether BCG vaccination and reduced COVID-19 mortality are causally related. An additional question is why different BCG strains may be variably associated with mortality.